Pavement smoothness of asphalt concrete overlays. Issue Volume 20:Issued 1(2019) (2nd January 2019) - Yildirim, Yetkin; Saygili, Gökhan
ABSTRACT: Nine asphalt concrete overlays were prepared using three different mix designs: Type C, 12.5 mm Superpave, and Coarse Matrix High Binder Hot-Mix (CMHB-C) mixtures and three different coarse aggregate: siliceous gravel, quartzite and sandstone. Pavement overlays were placed on field sections constructed along IH-20 in Harrison County, Texas. Field sections included each of the nine different surface mixture types. The base course was the same for all surface mixtures and was designed with 90% limestone and 10% local field sand. For all mixtures including the base course, PG 76-22 binder was used. Three pavement condition surveys were conducted on the outside lanes of eastbound and westbound field sections; immediately after, after two years, and after three years of the construction of asphalt concrete pavement system. IRI values were estimated from the left and right wheel paths. Each data-set was analysed separately to compare the pavement smoothness of different asphalt concrete overlays. Section 3 (Superpave quartzite mix) in the westbound lanes and Section 4 (CMHB-C gravel mix) in the eastbound lanes showed the best ride qualities. A paired t -test was conducted for each section in order to assess changes in IRI values with time under real traffic conditions. Test results and statistical analyses indicated that except for the IH-20 westbound left lanes of field Section 3 (i.e. Superpave quartz mix) the IRI values of the asphalt concrete overlays were time stable over the research period of three years.